Hubungan Status Gizi Terhadap Kebugaran Jasmani Pada Siswa Pelajar - Kusmiyati Kusmiyati; Dian Imam Saefulah; Dennis Guna Bawana (Lembaga Pengembangan Kinerja Dosen, 2021)
The Literature Review research aims to find out whether nutritional status influences physical fitness in students by using secondary data, namely previous research journal articles. The data collection technique uses the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) method. Searching for journal articles in literature reviews uses methodology with the criteria (1) Searching for journal article data to be reviewed according to the research title, (2) Research variables used according to writing needs, (3) Searching for articles with a time period of 2018-2022 or a period of 5 years, (4) The results of the research are measured validly, (5) Data analysis is analyzed appropriately. The database used by researchers was from Google Scholar Eric Journal and Taylor and Francis with keywords (the relationship between